Gender differences in acculturative stress of international students: A meta-analysis - Alzukari, Rawan; Wei, Tianlan (Journal of International Students, 2024)
This meta-analysis examines gender differences in acculturative stress among international students. Despite numerous studies on cultural adjustment, inconsistencies persist regarding gender differences in acculturative stress. This study synthesizes findings from 12 empirical studies. Comprehensive searches across databases, including institutional libraries, Google Scholar, PsycINFO, ScienceDirect, and ResearchGate, were conducted. Studies were categorized by geographic location, publication type, sample size, instruments, and participant age. The meta-analysis revealed no significant differences in acculturative stress levels between male and female international students. These findings suggest the need for further research on gender differences and other variables related to acculturative stress. Understanding these variables could enhance interventions and support international students’ well-being and adaptation.